HETEROTIC PATTERNS IN RAPESEED (BRASSICA NAPUS L.): CROSSES BETWEEN SPRING-TYPE AND WINTER-TYPE GENOTYPES - Rameeh, Valiollah (Journal of Agricultural Sciences (Belgrade), 2023)
Genetic improvement in a crop viz. brassica species through plant breeding essentially require existence of adequate genetic diversity within the gene pool. Winter rapeseed is known to be genetically diverse from spring rapeseed and, therefore can be used for extending of genetic diversity in the progenies which yielded via crossing methods. Line×tester analysis of two spring type of testers and six lines of winter type rapeseed varieties were used to estimate heterotic patterns of phenological traits, plant height and seed yield. Significant mean squares of parent vs crosses revealed significant heterosis for all the traits. Line×tester mean square which indicating the non-additive genetic effects was only significant for plant height and seed yield. High narrow sense heritability estimates for phenological traits indicating the prime importance of additive genetic effects and therefore, efficiency of selection for improving these traits. Due to significant and positive heterosis effects expression for phenological traits and plant height over winter parents, concluded that F1 progenies were more early maturity and shorter than winter parents. F1 progenies were also early flowering, early maturity and taller than spring type parents. Significant positive heterosis of crosses for seed yield over spring and winter parents were detected 75 and 42 percentages of F1 progenies, respectively, indicating more yield potential F1 hybrids than the spring and winter type parents.